Factors Associated with Treatment Adherence in Children with Attention Deficit Hyperactivity Disorder - Safavi, Parvin (Indian J Psychol Med, 2019)
BACKGROUND: Attention deficit/hyperactivity disorder (ADHD) is a common psychiatric disorder in children. The aim of this study was to investigate factors related to treatment adherence in children with ADHD. METHODS: This cross-sectional study was done in 118 children (aged 6–12 years) with ADHD who have been on medications for at least 6 months. The patients were selected based on the convenience sampling method from those who were referred to child psychiatry clinic. Medication Adherence Report Scale, Belief about Medicines Questionnaire specific version, and Children Symptom Inventory-4 were completed by parents and teachers. FINDINGS: Medication adherence had significant negative correlation with inattention scores on teacher-report forms (r = -0.27, P= 0.003) and poor economic status (P = 0.03). There was a positive correlation between medication adherence and history of psychopharmacological treatment in the family (P = 0.01), and father's education level (P = 0.001). Treatment adherence had no significant correlation with age, gender, comorbid disorders, mother's education, family history of ADHD, medication side effects, or parental concerns and beliefs about the necessity of drug use. CONCLUSION: The factors found to have a correlation with adherence should be taken in to account by clinicians so that adherence can be improved in their patients.